Histology Changes in the Mucosal Lining of the Gall Bladder Specimens from Patients of Tertiary Care Center - Makaju, Sarbada; Hirachan, Suspana; Chaudhary, Sonam; Rai, Chandra Kala; Alam, Munna (Journal of Nobel Medical College, 2026)
Background: The gallbladder is a hollow, pear-shaped organ situated in the gallbladder fossa on the inferior surface of the liver. It consists of mucosa, muscularis externa and adventitia. The recognizing histological changes in gallbladder is crucial for early detection of precursor lesions that may progress to cancer.Materials and Methods: This descriptive study was conducted in the Department of Pathology at Kathmandu Medical College and Teaching Hospital from 20 April 2025 to 20 July 2025 after ethical approval from the Institutional Review Committee (Ref no. KMC-IRC 02042025/14). A total of 399 cholecystectomy reports were included after taking the verbal consent. Data were entered in Microsoft Excel and analyzed using SPSS version 25.Results: The total number of 399 samples were collected. The total participants, 282 (70.7 %) were female and 117 (29.3%) were male. In this study most of the samples were from participants younger than 40 years. In the gross findings the most of the specimens consist of the normal wall but the >40 years had thickened wall 4 (1.7%). In case of the mucosa Ulcerated was second common in both genders. The microscopic findings showed that the epithelium was normal in maximum specimens (262, 65.7%), followed by ulcerated mucosa (94, 23.6%).Conclusion: The gall bladder specimen showed normal epithelium in most of the cases after cholecystectomy. The abnormal changes include varicosities in smooth muscles, epithelial ulceration and pyloric metaplasia in smooth muscle.